2013
DOI: 10.1111/chd.12112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing Practices in Infants with Congenital Heart Disease

Abstract: This single institution study identified that only 25% of infants with CHD underwent cytogenetic testing, indicating possible underutilization of testing in this age group. The high multiple testing rate indicates a need for improved guidelines for cost effective testing approaches. The diagnostic yield in this study suggests that CMA is a particularly useful first screening test when a specific syndrome is not clinically identifiable. Larger studies investigating cardiac lesion-specific diagnostic yield in is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 30 publications
(66 reference statements)
1
49
0
5
Order By: Relevance
“…Therefore, use of CMA as a higher fidelity option for firstline CHD genetic testing has been recommended, particularly when extra-cardiac features are present and a suspected diagnosis is lacking 61 . This opinion has been strongly supported by additional clinical and research studies assessing diagnostic yields in selected cohorts 55,56,[62][63][64][65] . In our retrospective analysis, CMA testing detected cytogenetic abnormalities of clinical or unknown significance in 35/121 (29%) infants with CHD 56 , representing rates on par with those observed in patients undergoing testing for intellectual disability 66,67 , for which CMA is already a first-line diagnostic test.…”
Section: Genetic Testing and Emerging Technologiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, use of CMA as a higher fidelity option for firstline CHD genetic testing has been recommended, particularly when extra-cardiac features are present and a suspected diagnosis is lacking 61 . This opinion has been strongly supported by additional clinical and research studies assessing diagnostic yields in selected cohorts 55,56,[62][63][64][65] . In our retrospective analysis, CMA testing detected cytogenetic abnormalities of clinical or unknown significance in 35/121 (29%) infants with CHD 56 , representing rates on par with those observed in patients undergoing testing for intellectual disability 66,67 , for which CMA is already a first-line diagnostic test.…”
Section: Genetic Testing and Emerging Technologiesmentioning
confidence: 88%
“…In addition, there is evidence that genetic testing is frequently underutilized in infants with CHD 55,56 . Nevertheless, the importance of genetic evaluation of patients with CHD has been emphasized in a position statement from the American Heart Association 57 , which cites four specific reasons to pursue testing:…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…Her analysis of genetic testing practices and results from diagnostic tests conducted on 1,087 infants with echocardiogram-diagnosed CHD found that only 25% of them had any form of genetic testing. Of those tested, 11% had aCGH, which identified abnormalities in 29% of that group, while 49% of patients had apparently isolated CHD [Connor et al, 2013]. The study by Connor and colleagues provides data complementary to that collected by Bachman et al on critically ill newborns, says Dr. Lin.…”
Section: The Studymentioning
confidence: 84%
“…Genetic factors often cause CHD, but newborns and older children with the condition who could benefit from genetic testing do not always receive it [Connor et al, 2013]. For patients with CHD in cardiac intensive care units (CICUs) who do, aCGH is preferable to chromosome analysis because it can detect more potential genetic causes, write researchers at the University of Pittsburgh in Pennsylvania [Bachman et al, 2013].…”
mentioning
confidence: 99%
“…tested, 11% had aCGH, which identified abnormalities in 29% of that group, while 49% of patients had apparently isolated CHD [Connor et al, 2013]. The study by Connor and colleagues provides data complementary to that collected by Bachman et al on critically ill newborns, says Dr. Lin.…”
mentioning
confidence: 78%